Improving Students' Communication Skills Using Student Worksheets on Nervous System Concepts - Isus Yusrina Azizah; Soesy Asiah Soesilawaty; Rr Marhamah (Jurnal Pendidikan Indonesia Gemilang, 2023)
This study aimed to improve students' communication skills by applying student worksheets. This research is class action research. The research was conducted at a high school in Bandung, Indonesia. The research subjects were class XI Math and Science students consisting of 13 male and 13 female students. The research was conducted for two cycles. Each research cycle involves planning, action, observation, and reflection. The research data includes students' written communication skills and the implementation of the syntax of teaching and learning activities taking place. Data analysis techniques were carried out using descriptive comparative and critical analysis. Research procedures include planning, action, observation, and reflection. The results showed an increase from Cycle I, and Cycle II resulted in an average increase in communication skills (Cycle I/Cycle II) of (62.7%/ 81.9%). Based on the research results, student worksheets can improve communication skills by 19.2%.